The Effect of PAD and Balanced Funds on Human Development Index in Yapen Islands District - Rinaldo Piris; Waspada Meliala (Budapest International Research and Critics University, 2022)
The growth of Regional Original Income (PAD) of Yapen Islands Regency in 2011 to 2015, has increased from year to year with an average growth of 32.33% per year. Meanwhile, the growth of the Yapen Islands District Balance Fund in 2011 to 2015, has increased from year to year with an average growth of 9.77% per year. The correlation coefficient value obtained is 0.946 or 94.6% and is close to positive one. The research method is qualitative. The results of the study show that the Regional Original Income, and the Balancing Fund has a significant influence on the Yapen Islands Regency Human Development Index (IPM) or the size of the Human Development Index (IPM) is strongly influenced by the size of the Regional Original Income and the Balancing Fund. The factors that also affect the Human Development Index (HDI) in Yapen Islands Regency are as follows; Aspects of Education (literacy and length of schooling), health aspects (life expectancy) and economic aspects (purchasing power parity).